Results of Arthroscopic Revision Rotator Cuff Repair for Failed Open or Arthroscopic Repair: A Prospective Multicenter Study on 100 Cases. Issue 8 (July 2022) - Hackl, Michael; Flury, Matthias; Kolling, Christoph; Nebelung, Wolfgang; Krauss, Christine A.; Kraemer, Nils A.; Heuberer, Philipp R.; Laky, Brenda; Wellmann, Mathias; Pastor, Marc-Frederic; Imhoff, Andreas B.; Reuter, Sven; et al.
Background: Retears after rotator cuff repair (RCR) have been associated with poor clinical results. Meaningful data regarding the role of arthroscopic revision RCR are sparse thus far. Purpose/Hypothesis: To investigate results after arthroscopic revision RCR. We hypothesized that (1) arthroscopic revision RCR would lead to improved outcomes, (2) the clinical results would be dependent on tendon integrity and (3) tear pattern, tendon involvement, and repair technique would influence clinical and structural results. Study Design: Case series; Level of evidence 4. Methods: During a 40-month period, 100 patients who underwent arthroscopic revision RCR were prospectively enrolled in this multicenter study. Outcomes were evaluated preoperatively, at 6 months (6M), and at 24 months (24M) using the Constant score (CS), the Oxford Shoulder Score (OSS), and the Subjective Shoulder Value (SSV). Tendon integrity at 2 years was analyzed using magnetic resonance imaging. A total of 13 patients (13%) were lost to follow-up, and 14 patients (14%) had a symptomatic retear before the 24M follow-up. Results: All clinical scores improved significantly during the study period (CS: preoperative, 44 ± 16; 6M, 58 ± 22; 24M, 69 ± 19 points; OSS: preoperative, 27 ± 8; 6M, 36 ± 11; 24M, 40 ± 9 points; SSV: preoperative, 43% ± 18%; 6M, 66% ± 24%; 24M, 75% ± 22%) ( P < .01). At 2 years, a retear rate of 51.8% (43/83) and a surgical revision rate of 12.6% (11/87) were observed. Mean full-thickness tear size decreased from 5.00 ± 1.61 cm 2 to 3.25 ± 1.92 cm 2 ( P = .041). Although the Sugaya score improved from 4.5 ± 0.9 to 3.7 ± 1.4 ( P = .043), tendon integrity did not correlate with better outcome scores. Previous open RCR, involvement of the subscapularis, chondral lesions of Outerbridge grade ≥2, and medial cuff failure were correlated with poorer SSV scores at 2 years ( P ≤ .047). Patients with traumatic retears had better CS and OSS scores at 2 years ( P ≤ .039). Conclusion: Although arthroscopic revision RCR improved shoulder function, retears were frequent but usually smaller. Patients with retears, however, did not necessarily have poorer shoulder function. Patient satisfaction at 2 years was lower when primary open RCR was performed, when a subscapularis tear or osteoarthritis was present, and when the rotator cuff retear was located at the musculotendinous junction. Patients with traumatic retears showed better functional improvement after revision.